2018
DOI: 10.3389/fenvs.2018.00109
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of the Geostationary Carbon Cycle Observatory (GeoCarb) to Provide Multi-scale Constraints on the Carbon Cycle in the Americas

Abstract: The second NASA Earth Venture Mission, Geostationary Carbon Cycle Observatory (GeoCarb), will provide measurements of atmospheric carbon dioxide (CO 2), methane (CH 4), carbon monoxide (CO), and solar-induced fluorescence (SIF) from Geostationary Orbit (GEO). The GeoCarb mission will deliver daily maps of column concentrations of CO 2 , CH 4 , and CO over the observed landmasses in the Americas at a spatial resolution of roughly 10 × 10 km. Persistent measurements of CO 2 , CH 4 , CO, and SIF will contribute s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 56 publications
0
85
0
Order By: Relevance
“…For Riyadh, Cairo, and LA, the ratios between emission at about the satellite overpassing time against the monthly average value are about 1.195, 1.127, and 1.288, corresponding to biases of about +19.5%, +12.7%, and +28.8% by only sampling in daytime compared to the monthly total emissions. More space observation missions including the Geostationary Carbon Cycle Observatory (GeoCarb) (Moore et al, 2018), OCO‐3 (Eldering, Wennberg, et al, 2017), and MicroCARB (https://microcarb.cnes.fr/en/MICROCARB/GP_mission.htm) will further enhance the uniform sampling over urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…For Riyadh, Cairo, and LA, the ratios between emission at about the satellite overpassing time against the monthly average value are about 1.195, 1.127, and 1.288, corresponding to biases of about +19.5%, +12.7%, and +28.8% by only sampling in daytime compared to the monthly total emissions. More space observation missions including the Geostationary Carbon Cycle Observatory (GeoCarb) (Moore et al, 2018), OCO‐3 (Eldering, Wennberg, et al, 2017), and MicroCARB (https://microcarb.cnes.fr/en/MICROCARB/GP_mission.htm) will further enhance the uniform sampling over urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…Observations of atmospheric composition focused on air quality are now moving from only LEO missions to include an internationally coordinated GEO component to the constellation that will be in place in the early 2020s (CEOS‐ACC, ). A coordinated GEO component to a constellation of greenhouse gas missions from multiple nations may soon materialize (Crisp et al, ), beginning with NASA's planned Geostationary Carbon Cycle Observatory (GeoCARB; Moore et al, ). For both air quality and greenhouse gases, the synergy of a LEO‐GEO constellation is highly desirable, but results in a gap in continuous observations at high latitudes over the ABZ.…”
Section: Highly Elliptical Orbits For Remote Sensing Of the Abz (Ray mentioning
confidence: 99%
“…This virtual constellation will consist of satellites from multiple countries coordinated by the Committee on Earth Observation Satellites (CEOS) Atmospheric Composition Virtual Constellation (AC-VC) group (CEOS-ACC 2011). A coordinated constellation architecture is also emerging for GHGs , with many existing and planned LEO missions, NASA's GeoCarb as the first GEO GHG mission to launch around 2022 (Moore et al 2018) and missions such as the Geostationary Emission Explorer for Europe (G3E/ARRHENIUS) (Butz et al 2015) considered by other space agencies. A coordinated GHG constellation would enable major advances in carbon cycle monitoring, including both natural and anthropogenic sources, in support of the UNFCCC Paris Agreement.…”
Section: Orbitsmentioning
confidence: 99%
“…ESA's SCIAMACHY (Buchwitz et al 2005), NASA's Orbiting Carbon Observatory 2 (OCO-2) (Crisp et al 2004) and ESA's Tropospheric Monitoring Instrument (TROPOMI) have demonstrated the capabilities of dispersive/grating spectrometers for measuring CO 2 , CH 4 , CO and SIF from LEO and NASA's GeoCarb will use a grating spectrometer to observe these species from GEO (Moore et al 2018). A grating spectrometer is also a possibility for AIM-North and in fact, our dispersive band selection and spectral sampling in Table 4 is based directly on plans for GeoCarb (O'Brien et al 2016).…”
Section: Near-infrared and Shortwave Infrared (Nir-swir) Spectrometermentioning
confidence: 99%